(untitled) (Interdisciplinary Studies Journal, 2025)
The general objective of this study is to understand the effectiveness of the Childcare Assistance program at the Federal Rural University of the Semi-Arid Region (UFERSA) concerning the material and symbolic retention of beneficiaries, taking into account the perspectives of student beneficiaries and professionals from the Student Assistance Office (PROAE). The specific objectives include contextualizing the trajectory of student assistance in Brazil and at UFERSA and evaluating the Childcare Assistance program in comparison to other student assistance policies offered by the institution. Employing qualitative, descriptive, and exploratory approaches, a case study research was conducted, involving interviews, document analysis, and observation. Seven student mothers and five PROAE staff participated in the study. The results underscore the importance of Daycare Assistance in ensuring the material permanence of beneficiaries, despite its financial inadequacy and the lack of accumulation with other paid activities which negatively impacts academic performance. Regarding symbolic permanence, there is a shortage of initiatives promoting a sense of belonging and integration in academic life. Consequently, it is concluded that student assistance should extend beyond financial support to address the needs of student mothers and facilitate broader engagement in academic life, considering both material and symbolic aspects.